Measuring What Matters: Assessing Creativity, Critical Thinking, and the Design Process. Issue 3 (July 2018) - Shively, Kate; Stith, Krista M.; Rubenstein, Lisa DaVia
The field of gifted education has a rich history of proposing and implementing innovative pedagogical practices to develop students' creative and critical thinking, yet less attention has been given to the assessment of these learning experiences. If creative and critical thinking are both inherently important in developing global problem solvers and further represent the goals of gifted curriculum, then classroom assessments must be designed to measure student development of these process skills. Many assessment rubrics emphasize the end product or superficially address process skills. This article provides sample rubrics to assess creative and critical thinking skills independently. Then, we consider anchoring larger projects' assessment within the Design Thinking Model (DTM), which embeds creative and critical thinking skills into the design process. Teachers may tailor these rubrics to assist in measuring the essential, yet complex, cognitive processes, and clearly convey to students the characteristics and practices of a good thinker and designer.